(untitled) (Journal of Hama University, 2019)
Procedures of preparation and restoration of dental Caries could cause irreversible undesired negative side effects on dental pulp vitality. The acuity effects are according to several factors, such as resin restorations monomers penetration into remaining dentin layer (RDL) protecting dental pulp. The aim of this study is to investigate the influence of some composite restorations variables, on healthy status of dental pulp. Human teeth, scheduled for orthodontic extraction, have been used, and followed clinically and histologically. The teeth are divided to (8) groups (n=10) to study the effects of (RDL) thickness, dentin etching technique and composite light-curing period, on dental pulp’s healthy status. Clinically, the results are controlled: after 2 and 8 weeks. Dental pulp pain was classified according the acuity characters. Histologically, dental pulp health was controlled after 8 weeks and classified according to pulp disorders. Proper negative and positives controls were used. Statistical Analysis (P<0.05) show significant differences between certain studied groups mainly regarding (RDL) thickness. Specimens with low (RDL) thickness and short light-curing period show the worst pulpal pathologic reactions, especially when total-etch technique was used. In contrast, pulpal pathologic disorders were significantly less in specimens with high (RDL) thickness and long light-curing period especially when self-etching technique was used. We conclude that low (RDL) thickness requires proper light-curing period, to improve conversion rate of polymerization, in order to avoid free monomers’ dentinal penetration. It is recommended, in such cases, to use self-etching technique which realizes mild dentin permeability compatible to dental pulp.